Blended learning berbasis project-based learning untuk meningkatkan kemampuan berpikir kritis - Fendy Hardian Permana; Lise Chamisijatin; Siti Zaenab (University of Muhammadiyah Malang, 2021)
Today’s technology plays a critical role in human activities, including education. However, it is shown that the integration of technology into education did not improve students’ critical thinking skills. This study aims to determine the effect of blended learning through Edmodo based on project-based learning (PBL) to improve critical thinking skills. Quantitative approach was employed with a quasi-experimental method. Samples of this research were students of the undergraduate Biology Education Program, Universitas Muhammadiyah Malang. These samples took Learning Strategy subject with class A as the experimental group, and class B as the control group. Results show that blended learning based on PBL significantly improved students’ critical thinking skills.